2023
DOI: 10.3390/polym15143018
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Multivariate Statistical Control Chart and Machine Learning to Identify the Abnormal Process Parameters for Polylactide with Glass Fiber Composites in Injection Molding; Part I: The Processing Parameter Optimization for Multiple Qualities of Polylactide/Glass Fiber Composites in Injection Molding

Abstract: This paper discusses the mixing of polylactide (PLA) and glass fiber which use injection molding to produce a functional composite material with glass fiber properties. The injection molding process explores the influence of glass fiber ratio, melt temperature, injection speed, packing pressure, packing time and cooling time on the mechanical properties of composite. Using the orthogonal table planning experiment of the Taguchi method, the optimal parameter level combination of a single quality process is obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The ANOVA results for the influence of each control factor on the double-cured polyurethane hot-melt adhesive are shown in Table S8 (Supplementary Document) . The ANOVA was needed after the main effect analysis was completed for further confirmation of the significance and magnitude of the effect of each control factor [ 34 ]. The ANOVA showed that three important factors which affect the shear strength with F-values are, accordingly, the NCO:OH ratio, with an F-value of 362.33, the photocurable monomer, with an F-value of 42.37, and the polyol, with an F-value of 18.11 (if the F-value > 5, it is important, but if the F-value < 5, it is not important), which is consistent with the results obtained from the main effect analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ANOVA results for the influence of each control factor on the double-cured polyurethane hot-melt adhesive are shown in Table S8 (Supplementary Document) . The ANOVA was needed after the main effect analysis was completed for further confirmation of the significance and magnitude of the effect of each control factor [ 34 ]. The ANOVA showed that three important factors which affect the shear strength with F-values are, accordingly, the NCO:OH ratio, with an F-value of 362.33, the photocurable monomer, with an F-value of 42.37, and the polyol, with an F-value of 18.11 (if the F-value > 5, it is important, but if the F-value < 5, it is not important), which is consistent with the results obtained from the main effect analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The S / N ratios were calculated for each experimental group using the obtained results from the peel strength analysis through the use of LTB characteristics [ 34 ], and they are presented in Table 8 . The response table and response plot of the main effect analysis are shown in Table 9 and Figure 9 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In orthogonal test, range analysis is often used to determine the influence of various factors on the results 49,50 . The above research shows that nozzle temperature, printing speed, extrusion width, and printing layer height will affect the mechanical properties of the specimen.…”
Section: Resultsmentioning
confidence: 99%